IMPLEMENTASI PERATURAN BUPATI LINGGA NOMOR 95 TAHUN 2020 TENTANG PENERAPAN DISIPLIN DAN PENEGAKAN HUKUM PROTOKOL KESEHATAN SEBAGAI UPAYA PENCEGAHAN DAN PENGENDALIAN CORONA VIRUS DISEASE 2019 DI KECAMATAN SINGKEP - Kukuh Saputro Jati; Emilda Firdaus; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
then this researcher is directed to study for the first stimulant, the implementation of theLingga Regent Regulation Number 95 of 2020 concerning the Implementation of Discipline andLaw Enforcement of Health Protocols as an Efforts to Prevent and Control Corona Virus Disease2019 in Singkep District, Second, the inhibiting factors for the implementation of the LinggaRegent's Regulation Number 95 of 2020 concerning the Implementation of Discipline and LawEnforcement of Health Protocols as an Effort to Prevent and Control the Corona Virus Disease2019 in Singkep District, Third, the efforts made to overcome the problems of implementing theImplementation of Discipline and Law Enforcement of Health Protocols as an Effort to Preventand Control the Corona Virus Disease 2019 in Singkep District.This research is a sociological legal research, because it is based on field research, namelyby collecting data from observations, interviews, and literature reviews that are related to theproblems studied, assisted by primary, secondary and tertiary data. This study uses qualitativedata analysis, produces descriptive data, and concludes with deductive thinking methods.The implementation for handling Covid-19 in the Singkep district is one of the tasks of theHealth Service, Population Control and Family Planning, Regional Disaster Management Agency,Civil Service Police Unit and Fire Department and Community Regional Revenue Agency inSingkep District by carrying out, Yustisi Patrol, Security and escort, Dissemination of Covid-19Health Protocols. People are no longer obedient to health protocols, especially in public places.the government must take firm action by conducting socialization.Keywords: Government Policy – Health Protocol – Corona Virus Disease